Performance and security evaluation of different RSA cryptography system implementations - Rosa, Ana Carla Quallio; Campiolo, Rodrigo; Batista, Daniel Macêdo (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.11863, 2025)
RSA remains one of the most prominent cryptographic systems for protecting systems and data. This study evaluates implementations of the RSA algorithm using different programming languages and libraries. The experiments were conducted in C, C++, Java, JavaScript, Python, and Rust. Rust, C, and Python implementations exhibited the shortest execution times for encryption and decryption. The analysis of data structures revealed similar patterns across languages. Memory dumps exposed fragments of the private key in several implementations, with full recovery possible in JavaScript. The results provide valuable insights for performance and security decisions in RSA implementations.